ANALYZING THE ROLE OF GOOGLE TRANSLATE IN COMPREHENDING ENGLISH TEXTS FOR THE 5th SEMESTER OF ENGLISH DEPARTMENT OF FKIP UKI TORAJA - Payangan, Synthia; Rachel, Rachel; Siumarlata, Viktor (Publikasi dan UKI Press UKI Toraja., 2025)
The purpose of this study is to determine the role of google translation in comprehending English text for 5th semester students of the English Department of FKIP UKI Toraja. In this study used qualitative methods in the form of interviews. To analyze the data, researcher used the theory of Miles and Hubberman. The source of data in this study is 5th semester students majoring in English. UKI Toraja consists of ten students as research reapondents. Through the results of the study, researcher found the role of Google Translate in comprehending English text, namely the speed and ease of translating Google Translate is able to provide an initial picture for a text, although it is limited in translating cultures, norms and social contexts. Based on the results above, the researcher concluded that Google Translate plays a role and is significance in comprehending English texts. Its role and significance include providing ease in translation process, providing quickly translation, allowing students to quickly get an overview of the text they are reading, time efficiency, facilitating cross-cultural communication.